International Capital Market Equilibrium and the Multinational Firm Financing and Investment Policies - Senbet, Lemma W. (Journal of Financial and Quantitative Analysis, 1979)
Lemma W. Senbet, International Capital Market Equilibrium and the Multinational Firm Financing and Investment Policies, The Journal of Financial and Quantitative Analysis, Vol. 14, No. 3 (Sep., 1979), pp. 455-480